Mind the ‘inequality’ gap: intersectionality-informed scoping review of inequalities and adverse experiences of health and care workers globally - Anuj Kapilashrami; Reza Majdzadeh; Roomi Aziz (BMJ Global Health)
Context Health and care workers’ well-being is critical for comprehensive human resources for health (HRH) planning. However, system-wide factors such as wage disparities and career advancement barriers remain underexplored, while most existing planning frameworks focus on gender, ignoring other interactions shaping the HRH experiences.Objective To systematically map literature on adverse HRH experiences, underlying inequalities and the resulting impact using an intersectional equity lens.Methods A rigorous scoping protocol was developed which guided the search in four bibliographic databases (SCOPUS, Web of Science, PubMed and CINAHL Ultimate). Literature was screened by two reviewers independently, charted and thematically analysed.Results From 21 184 records, 511 articles were included. 76% of the excluded articles were duplicates, while the rest were ineligible (non-English, grey literature, irrelevant publication type, etc). The review unpacked six types of adverse experiences (invisibilisation, disproportionate scrutiny, denial of opportunities, verbal abuse, physical abuse and sexual harassment) across 72 countries. 20 social locations, such as gender, race, ethnicity, cadre and their interactions shaped these experiences.55% of these studies were based in high-income countries and only 2% in low-income countries. 45% of articles studied these experiences across only two or more social locations, with the most common combinations being race–sex. Adverse manifestations included wage disparities, career advancement barriers, poor mental health and high turnover. The existing literature lacked an equity gaze, missing the underlying systematic drivers and rarely exploring intersecting unique positionalities of health and care workers.Implications Using an intersectionality lens, this scoping review identifies three key gaps: regional evidence imbalances, lack of an explicit intersectional equity focus and absence of translation of the scant intersectional evidence into HRH policy tools. These gaps restrict global HRH planning and hinder the development of inclusive, context-specific strategies—especially in low- and middle-income countries facing the most severe workforce challenges.